TMEM16F Expressed in Kupffer Cells Regulates Liver Inflammation and Metabolism to Protect Against Listeria Monocytogenes - Jianlong Tang; Hua Song; Shimin Li; Sin Man Lam; Jieming Ping; Mengyun Yang; Na Li; Teding Chang; Ze Yu; Weixiang Liu; Yan Lu; Min Zhu; et al. (Advanced Science)
Abstract Infection by bacteria leads to tissue damage and inflammation, which need to be tightly controlled by host mechanisms to avoid deleterious consequences. It is previously reported that TMEM16F, a calcium‐activated lipid scramblase expressed in various immune cell types including T cells and neutrophils, is critical for the control of infection by bacterium Listeria monocytogenes (Lm) in vivo. This function correlated with the capacity of TMEM16F to repair the plasma membrane (PM) damage induced in T cells in vitro, by the Lm toxin listeriolysin O (LLO). However, whether the protective effect of TMEM16F on Lm infection in vivo is mediated by an impact in T cells, or in other cell types, is not determined. Herein, the immune cell types and mechanisms implicated in the protective effect of TMEM16F against Lm in vivo are elucidated. Cellular protective effects of TMEM16F correlated with its capacity of lipid scrambling and augment PM fluidity. Using cell type‐specific TMEM16F‐deficient mice, the indication is obtained that TMEM16F expressed in liver Kupffer cells (KCs), but not in T cells or B cells, is key for protection against Listeria in vivo. In the absence of TMEM16F, Listeria induced PM rupture and fragmentation of KCs in vivo. KC death associated with greater liver damage, inflammatory changes, and dysregulated liver metabolism. Overall, the results uncovered that TMEM16F expressed in Kupffer cells is crucial to protect the host against Listeria infection. This influence is associated with the capacity of Kupffer cell‐expressed TMEM16F to prevent excessive inflammation and abnormal liver metabolism.